2008
DOI: 10.1681/asn.2007070813
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Atherosclerotic Plaque Formation Predicts Cardiovascular Events in ESRD

Abstract: Carotid intima media thickness (IMT) is a strong, independent predictor of cardiovascular events in both the general population and among those with end-stage renal disease (ESRD), but it is unknown whether changes in IMT or other ultrasound-measured indicators of atherosclerosis over time provide additional prognostic information. The progression of atherosclerosis with carotid ultrasound was followed in a cohort of 135 ESRD patients, 103 of whom had a repeat ultrasound after 15 mo of follow-up. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 21 publications
2
40
2
Order By: Relevance
“…Quantifying did not require special software (for a more sophisticated analysis, such as plaque area or volume) and also predicts cardiovascular events more accurately than cIMT (9). Benedetto et al (10) showed that progression of atheromatosis is a better predictor of cardiovascular events than the baseline number of plaques in a cohort of patients with ESRD, indicating that monitoring the evolution of plaque burden adds independent prognostic information. One novelty included in our study is the analysis of femoral arteries, which are not routinely explored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantifying did not require special software (for a more sophisticated analysis, such as plaque area or volume) and also predicts cardiovascular events more accurately than cIMT (9). Benedetto et al (10) showed that progression of atheromatosis is a better predictor of cardiovascular events than the baseline number of plaques in a cohort of patients with ESRD, indicating that monitoring the evolution of plaque burden adds independent prognostic information. One novelty included in our study is the analysis of femoral arteries, which are not routinely explored.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial ultrasonography assessment of subclinical atheromatosis is a noninvasive imaging technique that could predict incidence of cardiovascular events better than traditional models (6)(7)(8)(9). It has been shown that increases in plaque burden have a strong predictive value assessing cardiovascular events in patients on dialysis (10) and the general population (7). However, data on patients in early stages of CKD are scarce (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline in the risk for such events after transplantation occurs in the face of an increase in the prevalence of classic risk factors (2,3), and it is, therefore, mainly attributed to better control of CKD-related risk factors (4). Systemic inflammation as measured by C-reactive protein (CRP) is a powerful predictor of death (5) and progression of atherosclerosis in patients on dialysis (6). Biomarkers of CKD-mineral bone disorder (CKD-MBD)-including high serum phosphate and parathyroid hormone (PTH), low vitamin D, and high fibroblast growth factor 23 (FGF23)-are among the most indicted risk factors for the high rate of cardiovascular events in patients on dialysis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in IMT over time entails a parallel decrease in the risk for cardiovascular events, and this parameter is considered as a valid surrogate end point by the Food and Drug Administration (13) and the European Medicines Agency (14). The validity of IMT as a cardiovascular risk biomarker in the CKD population is supported by studies in patients with predialysis CKD (15) and patients on dialysis (6,16). In the sole longitudinal study focusing on IMT, this parameter regressed in parallel with PTH levels after renal transplantation (17).…”
Section: Introductionmentioning
confidence: 99%